Olive Oil as a Transport Medium for Bioactive Molecules of Plants?—An In Situ Study - Flemming, Jasmin; Meyer-Probst, Clara Theres; Hille, Kristin; Basche, Sabine; Speer, Karl; Kölling-Speer, Isabelle; Hannig, Christian; Hannig, Matthias (Molecules (Basel, Switzerland), 2023)
(1) Caries and erosions still remain a challenge for preventive dentistry. Certain plant extracts have shown beneficial effects in preventive dentistry. The aim of this study was to evaluate the antibacterial, anti-adherent and erosion-protective properties of ellagic acid (EA) as a polyphenolic agent. The combination with olive oil was investigated additionally to verify a possible improved bioactive effect of EA. (2) An in situ study was carried out with six subjects. Individual splints were prepared with bovine enamel specimens. The splints were worn for 1 min (pellicle formation time). Thereafter, 10 min rinses were performed with EA in water/in oil. Bacterial adherence was evaluated by fluorescence microscopy (DAPI, ConA, BacLight) after an 8 h oral exposition time. Additionally, the splints were worn for 30 min to quantify demineralization processes. The ultrastructure of the pellicle was investigated after an oral exposure time of 2 h under a transmission electron microscope. Statistical analysis was performed by Kruskal–Wallis tests, Mann–Whitney U tests and Bonferroni–Holm correction. (3) Rinsing with EA led to a significant reduction of adherent vital and dead bacteria. The combination with olive oil did not improve these outcomes. The assessment of glucan structures after rinsing with EA in water showed significant effects. Significant differences were observed for both rinses in calcium release at pH 3.0. After rinsing with EA in oil, significantly less calcium was released compared to rinsing with EA in water (pH = 3.0). (4) Olive oil is not suitable as a transport medium for lipophilic polyphenols. EA has anti-adherent and antibacterial properties in situ. EA also shows erosion-protective effects, which can be enhanced in combination with olive oil depending on the pH value. Ellagic acid has a neutral pH and could be an opportunity in the treatment of specific patient groups (xerostomia or mucositis).